Sistem Pendukung Keputusan Penerima Beasiswa Kurang Mampu Menggunakan Metode Profile Matching Pada SMA Negeri 1 Sungai Penuh - Cassia Putra , Bopy; Roestam , Rusdianto (Jurnal Manajemen Sistem Informasi, 2023)
The Smart Indonesia Program Scholarship Program (PIP) aims to provide access to academic potential to economically or economically disadvantaged communities to higher education to break the poverty chain. The program follows the receiver's pick-up philosophy. The selection process of prospective PIP scholarship recipients is based on criteria set by the Ministry of Research and Technology and Sma Negeri 1 Sungai Penuh. There are various steps in the decision support system, one of which is the profile matching procedure. The basic concept of the profile matching method assumes that the subject studied has an ideal level of predictor that must be met, and there is no minimum level that needs to be met or skipped. Checking is done using student data of prospective recipients of alternative scholarships standardized according to the type of criteria attribute. The calculation process provides the final result, i.e. the number of matrices normalized using weights per criterion. It shows the alternative ratings of grantees. The results of this study are expected to help decision-making in identifying poor grantees.